2010
DOI: 10.1002/pssc.200982493
|View full text |Cite
|
Sign up to set email alerts
|

ZnO films deposited by optimized PLD technique with bias voltages

Abstract: The pulsed laser deposition (PLD) technique with bias voltage application for formation of high quality ZnO films was investigated. Oxygen ambient in the PLD chamber significantly decreased the photoluminescence (PL) intensity of near band edge (NBE) emission. Then, instead of using oxygen ambient, the PLD technique with bias voltage application was optimized to attain the stoichiometric composition of the ZnO films. As the deposition temperature was increased, the X‐ray spectrum width diffracted from the (000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In this paper, we observed the saturation magnetization (M s ) of the ZnCoO:H films formed by changing the defect concentration using two techniques (the oxygen partial pressure and the PLD bias voltage [14]) and found that as the defect concentration was increased, M s significantly decreased but sometimes increased. We also found that the defect concentration certainly affected the saturation magnetization but it did so only through the shift of the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we observed the saturation magnetization (M s ) of the ZnCoO:H films formed by changing the defect concentration using two techniques (the oxygen partial pressure and the PLD bias voltage [14]) and found that as the defect concentration was increased, M s significantly decreased but sometimes increased. We also found that the defect concentration certainly affected the saturation magnetization but it did so only through the shift of the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
“…If positive (negative) ions were accelerated by a negative (positive) bias voltage on the grid, they would be decelerated by a positive (negative) bias voltage between the grid and the substrate. Accordingly, this bias voltage technique simply controlled the ratio of the positive and the negative ions without increasing their kinetic energy [14]. A Nd:YAG laser (266 nm) was utilized for the ablation; the pulse duration was 10 ns, the repetition rate was 10 Hz and the output energy was 75 mJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several techniques have been proposed to overcome these problems. Some examples include: using the pulsed laser deposition (PLD) technique to precisely control partial pressures of the oxygen ambient in the deposition chamber in order to attain the stoichiometric composition of ZnO films [3,4]; and applying bias voltages on the mesh grid in the deposition chamber in order to control the ratio of Zn and O ions which arrive at the substrates [5][6][7]. Various heterojunction structures have also been pro-posed to form n-type ZnO/p-type other semiconductors to avoid using p-type ZnO [8][9][10][11][12].…”
mentioning
confidence: 99%
“…An n-ZnO film was deposited on the n-ZnO substrate by the PLD technique with bias voltage application. The details of the bias voltage PLD system are described elsewhere [7]. If a positive bias voltage is applied on the grid electrode, positive ions (Zn 2+ ) are repelled and negative ions (O 2-) are attracted, while if a negative bias voltage is applied on the electrode, negative ions are repelled, and positive ions are attracted.…”
mentioning
confidence: 99%